Application of response surface methodology for the optimization of polycyclic aromatic hydrocarbons degradation from potable water using photo-Fenton oxidation process - Abd Manan, T.S.B. (2019)
Polycyclic aromatic hydrocarbons (PAHs) are carcinogenic compounds, composed of benzene rings. The objective of this research was to identify the optimum condition for the degradation of PAHs contaminated water using photo-Fenton oxidation process via response surface methodology (RSM). Aqueous solution was prepared and potable water samples were collected from water treatment plants in Perak Tengah, Perak, Malaysia in September 2016. The reaction time, pH, molarity of H 2 O 2 and FeSO 4 were analyzed followed by RSM using aqueous solution. A five level central composite design with quadratic model was used to evaluate the effects and interactions of these parameters. The response variable was the percentage of total organic carbon (TOC) removal. PAHs quantification was done using gas chromatography mass spectrometry analysis. The regression line fitted well with the data with R 2 value of 0.9757. The lack of fit test gives the highest value of Sum of Squares (15,666.64) with probability F value 0.0001 showing significant quadratic model. The optimum conditions were established corresponding to the percentage of TOC removal. The PAHs removal efficiency for potable water samples ranged from 76.4 to 91 following the first order of kinetic rates with R 2 values of >0.95. Conventional water treatment techniques are not effective for PAHs removal. Thus, advanced oxidation processes may be considered as an alternative to conventional water treatment techniques in Malaysia and other developing countries. Â© 2019 Elsevier B.V.